Interplay Between J‐ and H‐Type Coupling in Aggregates of π‐Conjugated Polymers: A Single‐Molecule Perspective. Issue 52 (6th November 2019) - Eder, Theresa; Vogelsang, Jan; Bange, Sebastian; Remmerssen, Klaas; Schmitz, Daniela; Jester, Stefan‐S.; Keller, Tristan J.; Höger, Sigurd; Lupton, John M.
Abstract: Strong dipole–dipole coupling within and between π‐conjugated segments shifts electronic transitions, and modifies vibronic coupling and excited‐state lifetimes. Since J‐type coupling between monomers along the conjugated‐polymer (CP) chain and H‐type coupling of chromophores between chains of a CP compete, a superposition of the spectral modifications arising from each type of coupling emerges, making the two couplings hard to discern in the ensemble. We introduce a single‐molecule H‐type aggregate of fixed spacing and variable length of up to 10 nm. HJ‐type aggregate formation is visualized intuitively in the scatter of single‐molecule spectra. Abstract : Coupling therapy : In organic electronics, J‐type coupling between monomers along the chain and H‐type coupling of chromophores between chains compete, which makes the two types of coupling hard to discern in the ensemble. A single‐molecule H‐type aggregate of fixed spacing and variable length of up to 10 nm is introduced, and HJ‐type aggregate formation is visualized intuitively in the scatter of single‐molecule spectra.